2015
DOI: 10.1063/1.4921050
|View full text |Cite
|
Sign up to set email alerts
|

Determination of threshold electric field for charge injection in polymeric materials

Abstract: Accurately determining the threshold electric field at which charge injection from the electrodes starts is important for reliable operation of dielectric materials as the presence of charge in the material can lead to electric field enhancement, resulting in degradation and early failures of the material. The two methods in charge measurements that have been commonly used to find out the threshold field have been compared to the proposed method, which overcomes the drawbacks of the two methods. Such method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…3 gives space charge dynamics during the volts-on period. In order to obtain the injected space charge profiles in the bulk, the subtraction method was employed to eliminate the capacitive charges on two electrodes 31 , as in Fig. 4.…”
Section: Space Charge Results and Calculationmentioning
confidence: 99%
“…3 gives space charge dynamics during the volts-on period. In order to obtain the injected space charge profiles in the bulk, the subtraction method was employed to eliminate the capacitive charges on two electrodes 31 , as in Fig. 4.…”
Section: Space Charge Results and Calculationmentioning
confidence: 99%
“…The injection of charge carriers occurs at the interface between the conductor and the insulator when the applied electric field is higher than the threshold field. From the previous work done by Liu et al [13], a value of threshold electric field about 10 kV/mm has been identified for charge injection in polyethylene. In this study, when the applied field exceeds the critical value (10 kV/mm), the boundary condition is defined by the Schottky injection at both electrodes.…”
Section: Continuity Equationmentioning
confidence: 99%
“…1(a) and 1(d) give the space charge dynamics during the voltson period. In order to obtain the injected space charge in the bulk, subtraction method was employed to eliminate the capacitive charges on two electrodes [10], as in Figs …”
Section: Space Charge Results and Calculation Of Charge Amountmentioning
confidence: 99%